Nilai-nilai Pendidikan dalam Tradisi Yasinan dan Air sebagai Sarana Penyembuhan pada Masyarakat Kampung Lebakwangi Ciamis - Siti Jubaedah (Attractive : Innovative Education Journal, 2024)
This research aims to reveal the educational values ​​contained in the Yasinan tradition and the use of water as a means of healing in the community of Lebakwangi Village, Ciamis. The Yasinan tradition, which is carried out regularly by the local community, not only functions as a spiritual means through the recitation of Surah Yasin, but also has social and religious educational values ​​that shape the character of the community. In addition, the water used in this tradition is believed to have healing powers, both physical and psychological, through the beliefs and prayers attached to it. This research uses a qualitative approach with ethnographic methods, through participant observation and in-depth interviews with religious leaders and local communities. The research results show that the educational values ​​contained in this tradition include increasing spirituality, social solidarity, discipline, and belief in divine power. This tradition also acts as an informal learning medium that teaches local wisdom and strengthens the cultural identity of the people of Lebakwangi Village.